2008
DOI: 10.1634/theoncologist.2007-0246
|View full text |Cite
|
Sign up to set email alerts
|

The CYP19 TTTA Repeat Polymorphism Is Related to the Prognosis of Premenopausal Stage I–II and Operable Stage III Breast Cancers

Abstract: After completing this course, the reader should be able to:1. Describe why premenopausal women with the long allele of the CYP19 TTTA repeat polymorphism have a greater survival rate and may not gain benefit from adjuvant chemotherapy.2. Assess whether we need to revisit the routine use of adjuvant chemotherapy in high-risk premenopausal patients with the long allele of the CYP19 polymorphism.3. Explain why further validation in a randomized study with a large sample size is needed to determine whether the CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Many prior studies from Korean people [17], Japanese people [18], and Caucasian people [19], all of that showed no significant correlation of CYP19 gene polymorphisms with the hazard of chocolate cysts or endometriosis. The study by Hirose et al, [20] showed that in estrogen biosynthesis, the genetic polymorphisms (CYP19A1) are as well expected to affect the degradation or synthesis of estrogen, and then, lead to increase the breast cancer risk at codon 39 [21,22], the (rs2236722) polymorphism is created by the substitution of amino acids (Trp) with (Arg), while another study showed the Japanese women with the presence of these different alleles (Arg) lead to significantly decreased the developing of the breast cancer risk [23]. In a survey by Leporati et al, the authors deal with the male patients with breast cancer and acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies from Korean people [17], Japanese people [18], and Caucasian people [19], all of that showed no significant correlation of CYP19 gene polymorphisms with the hazard of chocolate cysts or endometriosis. The study by Hirose et al, [20] showed that in estrogen biosynthesis, the genetic polymorphisms (CYP19A1) are as well expected to affect the degradation or synthesis of estrogen, and then, lead to increase the breast cancer risk at codon 39 [21,22], the (rs2236722) polymorphism is created by the substitution of amino acids (Trp) with (Arg), while another study showed the Japanese women with the presence of these different alleles (Arg) lead to significantly decreased the developing of the breast cancer risk [23]. In a survey by Leporati et al, the authors deal with the male patients with breast cancer and acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an aromatase inhibitor was reported to suppress cell growth and aromatase activity in lung A549 cells in vitro (30). A (TTTA) n repeat polymorphism in intron 4 of CYP19A1 was found to be associated with the risk of breast cancer (32) and the prognosis of patients affected by premenopausal breast cancer (20). Women with one 7-repeat allele (S allele) had lower plasma levels of estroneto-androstenedione ratio (32).…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes of ERa, rs2234693, as "C/C and T/C" vs. "T/T"; of COMT, rs4680, as "A/A and G/A" vs. "G/G," and of CYP17, rs743572, were grouped as "C/C" vs. "T/T and T/C." This grouping scheme has been commonly used in previous studies (20)(21)(22).…”
Section: Translational Relevancementioning
confidence: 99%
“…Breast cancer staging was conducted according to the American Joint Committee on Cancer (AJCC) criteria (the 6th Ed.). Patients' demographic information was collected from a genetic epidemiology study on the association between selected genetic polymorphisms and breast cancer in 482 patients, which was carried out at the same hospital (Huang et al, 2008). To avoid bias caused by the uncertain treatment effects of tamoxifen in tumors with weak ER and/or PR expression, 43 patients who did not receive adjuvant tamoxifen were excluded.…”
Section: Patients and Proceduresmentioning
confidence: 99%